2014 IEEE Globecom Workshops (GC Wkshps) 2014
DOI: 10.1109/glocomw.2014.7063572
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of network-assisted two-hop D2D communications

Abstract: Abstract-Network-assisted single-hop device-to-device (D2D) communication can increase the spectral and energy efficiency of cellular networks by taking advantage of the proximity, reuse, and hop gains. In this paper we argue that D2D technology can be used to further increase the spectral and energy efficiency if the key D2D radio resource management algorithms are suitably extended to support network assisted multi-hop D2D communications. Specifically we propose a novel, distributed utility maximizing D2D po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 12 publications
0
31
0
Order By: Relevance
“…In [12], authors consider multihop D2D communications in order to extend the network coverage and propose a resource allocation strategy to optimize the throughput along the multihop paths. The study is restricted to two-hop communications where one UE is identified as relay node for one pair of transmitting and receiving UE, where each hop is a unicast point-to-point (P2P) D2D transmission.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In [12], authors consider multihop D2D communications in order to extend the network coverage and propose a resource allocation strategy to optimize the throughput along the multihop paths. The study is restricted to two-hop communications where one UE is identified as relay node for one pair of transmitting and receiving UE, where each hop is a unicast point-to-point (P2P) D2D transmission.…”
Section: Related Workmentioning
confidence: 99%
“…Multihop D2D communications in LTE-A networks have been studied in several works, e.g., [12][13][14][15][16][17]. In [12], authors consider multihop D2D communications in order to extend the network coverage and propose a resource allocation strategy to optimize the throughput along the multihop paths.…”
Section: Related Workmentioning
confidence: 99%
“…Y enabling direct and low-power communication among users, hereafter generally referred as User Equipments (UEs), Device-to-Device (D2D) communication leads to an improved spectrum utilization, system capacity and/or Quality of Service (QoS) levels; and at cell boundaries, D2D links may be used as relays to extend the coverage area [1], [2].…”
mentioning
confidence: 99%
“…In addition, D2D communications in a cellular network are controlled by network operators. As a result, D2D communications in a cellular network typically assume 1-hop or 2-hop relay [5,10]. However, to fully utilize the potential of D2D communications, providing multihop D2D networks that operate autonomously is highly required.…”
Section: Introductionmentioning
confidence: 99%